Estudo das propriedades mecânicas e microestruturais de materiais cimentícios geopoliméricos produzidos a partir de metacaulim e escória de alto forno - ALMEIDA, Bianca Mendes (Universidade Federal do Pará, 2023)
The environmental impacts caused by the production of Portland Cement point to the urgency of reducing the use of this binder mainly due to the CO2 emission and energy consumption that occur during its production process. In the search for alternative materials, geopolymeric cement has shown promise, both in terms of mechanical performance and conservation of natural resources. These cements are obtained from natural raw materials containing aluminosilicates activated by an alkaline solution. In this work, geopolymeric cement paste, mortar and concrete were developed using metakaolin, blast furnace slag and alkaline solution of sodium hydroxide and sodium silicate. The main objectives included evaluating the influence of blast furnace slag on the mechanical properties of geopolymer pastes, varying its addition in mass (30% to 60%), evaluating the influence of sand in geopolymer mortar varying its addition in the paste with better performance of 20% to 70%, and finally, the addition of gravel 0 in two mixtures. The results showed that the paste reached a maximum compressive strength of 36.5 MPa with 35% slag in the matrix. This value rose to 41.15 MPa in the mortar with the incorporation of 40% sand. For concrete, the best result was found for the mixture that contained less crushed stone. The results of the concrete were compared with the CPV-ARI Portland cement concrete by setting some dosing parameters such as binder consumption and water/binder ratio. Other properties investigated included setting time, slump, flexural tensile strength and microstructural analysis by SEM. Geopolymeric concrete was superior to Portland by up to 21.16%, reaching compressive strength of 41.8 MPa, flexural traction of 4.87 MPa and better matrix/aggregate adhesion in the mixture with less addition of gravel 0. The results obtained for geopolymers enable their application in civil works that demand materials that reach high strenght in the initial ages, precast and paving industries.